Psychosocial and cognitive predictors of academic achievement among higher education students in Southern Ethiopia - Chalachew Kassaw; Valeriia Demareva (PLoS ONE, 2025)
Introduction Academic achievement is influenced by a combination of personal cognitive abilities, psycho-social resources, and educational context. Core cognitive functions such as working memory and inhibitory control support students’ ability to retain, process, and apply information, while coping strategies help manage academic stress. However, research integrating both psycho-social and cognitive predictors of academic success in low-resource university settings remains scarce. This study aimed to examine the combined psycho-social and cognitive correlates of academic achievement among higher education students in Southern Ethiopia. Methodology The study was conducted from August to November, 2024. A total of 30 undergraduate students participated in the study. Academic achievement was measured using Grade Point Average (GPA). Psychosocial factors were assessed with the Folkman and Lazarus coping inventory, the Adult ADHD Self-Report Scale (ASRS v1.1), the Bergen Social Media Addiction Scale (BSMAS), and the Dundee Ready Education Environment Measure (DREEM). Cognitive functions were evaluated using a two-back task (working memory) and a go/no-go task (inhibitory control). Data were analyzed using Spearman correlation, Mann–Whitney U test, Kruskal–Wallis test, multiple linear regression, and ANOVA. Results Sex differences were observed, with male students demonstrating higher GPA compared to female students. Faster reaction time in the two-back task was significantly associated with better GPA. Higher use of self-controlling coping strategies was marginally associated with GPA in regression modeling, but ANOVA indicated a significant contribution of this coping style to the explained variance in academic performance. Other psycho-social variables, including academic self-perception, social media addiction, and ADHD symptoms, were not significantly related to GPA. Overall, psycho-social factors, particularly coping strategies and gender, were stronger predictors of academic achievement than cognitive measures in this sample. Conclusion The findings highlight the critical role of coping mechanisms and gender differences in academic performance among Ethiopian university students. These results underscore the need for psycho-social support interventions alongside cognitive skills development to enhance academic success in low-resource educational environments.